Shipboard measurements of gaseous elemental mercury along the coast of Central and Southern California - Weiss-Penzias, P. S.; Williams, E. J.; Lerner, B. M.; Bates, T. S.; Gaston, C.; Prather, K.; Vlasenko, A.; Li, S. M. (JOURNAL OF GEOPHYSICAL RESEARCH-ATMOSPHERES, 2013)
Gaseous elemental mercury (GEM) in the atmosphere was measured during an oceanographic cruise in coastal waters between San Diego and San Francisco, California during the CalNex 2010 campaign. The goal of the measurements was to quantify GEM in the various environments that the ship encountered, from urban outflow, the Port of Long Beach and associated shipping lanes, coastal waters affected by upwelling, the San Francisco Bay, and the Sacramento ship channel. Mean GEM for the whole cruise was 1.41 +/- 0.20 ng m(-3), indicating that background concentrations were predominantly observed. The ship's position was most often in waters off the coast of Los Angeles (74% of time with latitude <34.3 degrees N) and mean GEM for this section was not significantly (P > 0.05) higher than the whole cruise mean. South of 34.3 degrees N, GEM was observed to vary diurnally and as a function of wind direction, displaying significantly higher concentrations at night and in the morning associated with general transport from the land to the sea. GEM and CO concentrations were positively correlated with a slope of 0.0011 ng m(-3) ppbv(-1) (1.23 x 10(-7) mol mol(-1)) during periods identified as ``Los Angeles urban outflow'', which given the inventoried CO emissions for the region, suggests a larger source of GEM than is accounted for by the inventory. The timing of the diel maximum in GEM (9:00 local time) was intermediate between the maxima of CO and NO2 (6:00) and that of NO and SO2 (10:00-12:00), suggesting that a mixture of urban and industrial sources were contributing to GEM. There was no observable postsunrise dip in GEM concentrations due to reaction with atomic chlorine in the polluted coastal atmosphere. On three occasions, significantly higher GEM concentrations were observed while in the Port of Long Beach (similar to 7 ng m(-3)), and analyses of wind directions, ratios of GEM with other copollutants, and the composition of single particles, suggest that these plumes originated from the local waste incinerator in the Port area. A plume encounter from a large cargo ship allowed for the estimation of a mass-based emission factor for GEM (0.05 +/- 0.01 mg kg(-1) fuel burned). GEM enhancements observed in the Carquinez Straits, were lower than expected based on the observed NOx/SO2 ratios in the plumes and emissions inventories of the nearest oil refineries. In a region north of Monterey Bay known for upwelling, GEM in the air was positively correlated with dimethyl sulfide (DMS) in seawater and in the air. Using the observed GEM/DMS(g) relationship and the calculated mean DMS ocean-atmosphere flux for the cruise, an ocean-atmosphere flux of GEM of 0.017 +/- 0.009 mu mol m(-2) d(-1) was estimated. This flux was on the upper end of previously reported GEM ocean-atmosphere fluxes and should be verified with further measurements of Hg species in seawater and air. Citation: Weiss-Penzias, P. S., E. J. Williams, B. M. Lerner, T. S. Bates, C. Gaston, K. Prather, A. Vlasenko, and S. M. Li (2013), Shipboard measurements of gaseous elemental mercury along the coast of Central and Southern California. J. Geophys. Res. Atmos., 118, 208-219, doi: 10.1029/2012JD018463.